Reimagining Transnational Relations: the Embodied Politics of Visiting Friends and Relatives Mobilities. Issue 7 (21st April 2015) - Humbracht, Michael
Abstract: Migrant populations are often viewed in terms of alterity despite being settled members of communities. The image of migrants in many western contexts is one of being poor or ethnically and religiously different. This image in turn often frames migrants as being non‐local. However, in reality, the local is not perceived and constructed through predetermined or essentialist subjectivity but through processes of constructing and negotiating borders of identity and place that incite people to shift between subject positions of local/visitor, host/guest, or tourist/migrant. This paper problematises the rigidity of social positions that underpin images of migrant populations as the other by examining the visiting friends and relatives (or VFR) practices of migrant residents in Malmö, Sweden. Whereas many studies of VFR build on a tourism‐migration dialectic and focus on migrants, this study uses mobility politics as an analytical lens to examine both migrant residents and their friends and family. This focus sheds light on how family and friend's mobility politics are connected to the perception and construction of the local, local selves, and others. The research findings demonstrate that migrant residents are not the other but are an embedded part of the city regularly attracting visitors to the area. Furthermore, during visits, lines between host and guest, migrant and tourist, and visitor and local are blurred. Residents and visitors, guided by the rules of hospitality, attribute new embodied meanings to tourist and migrant mobilities that strengthen and bound the imaginations of residents and visitors to transnational networks. The conclusions from the study also help shed light on migrant integration and potential avenues for working with integration in the future. Copyright © 2015 John Wiley & Sons, Ltd.